Owady występujące na olszy czarnej Alnus glutinosa (L.) Gaertn. w drzewostanach z objawami zamierania - Borowski, Jerzy; Piętka, Jacek; Szczepkowski, Andrzej (Leśne Prace Badawcze, 2012)
The study gives information on insects living on the black alder Alnus glutinosa (L.) Gaertn. in those 57 alder stands which exhibited the most severe signs of dying back. The surveys revealed the presence of 28 species of insects belonging to various different orders. The most common species were Agelastica alni , Xiphydria camelus , Xyleborinus attenuatus (Bland.) (= X. alni Nissima) and Saperda scalaris . It seems that none of the species of insects identified would be expected to cause die back of alder over a large area. However, it was confirmed that insects do participate in the process of dying back of alder stands.